Letter from Henry M. Morfit to James Curtis Booth, August 9, 1850 - Morfit, Henry Mason (1850)
Henry M. Morfit (1793-1865) writes to James Curtis Booth (1810-1888) with advice on the refining patent that his son, Campbell Morfit (1820-1897), and Booth hope to sell to the United States Mint. Morfit, a claims lawyer in Washington, D.C. and a political figure in the Andrew Jackson presidential administrations, appears to have served as go-between for Booth and his son, Campbell, in their efforts to interest the U.S. Mint in their process for refining gold.
Keywords: United States Mint; Mint of the United States; Booth, James Curtis, 1810-1888; Metals--Refining; United States. Assay Office, New York City; Morfit, Campbell, 1820-1897